Model Pemberdayaan Ekonomi Pesantren Berbasis Wakaf Produktif: Studi Kasus pada Pondok Pesantren Al Ihsan Al Murtadlo Bululawang - Wahab, Fatkhul; Fauziyah, Fauziyah; Ihsan, Moh. (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
Pesantren (Islamic boarding schools) play a strategic role as educational institutions in shaping character and empowering communities. However, many pesantren face significant challenges in terms of operational funding and institutional development. This study aims to: (1) analyze the utilization of productive waqf potential to promote economic self-reliance at Al Ihsan Al Murtadlo Islamic Boarding School in Bululawang, Malang; and (2) examine the management of productive waqf in supporting educational activities at the same institution. This research employs a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews with the pesantren leader, waqf managers (Kyai H. Ahmad Suryanto, Ustadz Bambang Haryanto, and Ustadz Ahmad Fatoni), and community leaders, supplemented by observation and documentation. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing using triangulation techniques. The findings reveal that Pondok Pesantren Al Ihsan Al Murtadlo has productively utilized waqf assets, including approximately 5,630 m² of agricultural land (3,060 m² for rice and sugarcane cultivation) and an operational cooperative. The annual budget allocation for productive waqf management reaches Rp103,000,000, with monthly operational costs of approximately Rp2,833,000. The income generated from these waqf activities is used to support operational needs, development of educational facilities, assistance for underprivileged students, and training for students.